THE IMPORTANCE OF CONSIDERING GCG AND CSR WHILE PURSUING CORPORATE SHARE VALUE - Martha Fani Cahyandito; Oktovianus Nawa Pau (Jurnal Bisnis Manajemen, 2017)
Many academic debates have been arising, either pro or contra, about the influence of GCG implementation against the implementation of CSR, which ultimately culminated in the increase in the price of the shares. Unfortunately, despite these debates, GCG implementation (GCG index) in Indonesia is still low compared to other Asian countries, even though GCG is considered as a form of the commitment of corporation, especially public companies who are listed on the Indonesia Stock Exchange, in showing responsibility and professionalism of its work to all stakeholders. This research is intended to give a more concrete perspectives regarding the influence of GCG toward CSR and on the value of the shares of these companies that are registered on the Indonesian Institute for Good Corporate Governance, namely companies that claim itself has been implementing GCG. The result of the study showed that there is indeed the influence of GCG implementation on CSR implementation and the increase in the price of the shares. But it is worth noting that the share price is more influenced by the GCG implementation than by CSR implementation. This shows that the Indonesian investors still give priority to the GCG indicators (commitment, competence, transparency, leadership, accountability, the ability to work together, independency, vision, mission and corporate values, independency, moral and ethics, justice, and strategy), more than the commitment of the company in conducting the CSR, in determining the shares purchasing decision.